A study on the deployment and acceleration of low carbon technologies - Kennedy, Matthew (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2013)
The work presented in this thesis is an investigation into the variables that are considered by consumers when selecting low carbon technologies (LCT) and the barriers that are encountered by implementers when deploying such technologies. This involves an exploration of approaches to accelerate low carbon technology across various jurisdictions and a methodological analysis that predicts the factors influencing consumer choice of low carbon technologies. The achievement of sustainable energy objectives requires policy makers to be informed of the considerations that consumers make prior to deploying low carbon technologies in their homes. This thesis ascertains the key factors that affect and inform consumer choice and proposes a framework that facilitates the international deployment of clean technology.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin.